El cruce de fronteras en La Genara y en Como cashora al sol de Rosina Conde. - Cota Torres, Édgar (2012)
In the novels titled La Genara and Como cashora al sol, Conde represents women in a context that limits them, and that at the same time offers them the possibility to decide for themselves and in that way be subjects of their own consequences. Her female characters opt to make the most of opportunities, if they wish to do so, and not be subjugated in a patriarchal society that sets them aside in their border social environment. This article analyses the diversity of borders crossed by the female protagonists in both novels. It will be observed in Conde's attempt to portray a reality that affects women, how women are in a state of liminality, ambiguity, and of transformation which contribute to the arrival to a zone where border crossings are constant.